A seed-mediated growth of gold nanoparticles inside carbon nanotube fibers for fabrication of multifunctional nanohybrid fibers with enhanced mechanical and electrical properties. Issue 12 (7th March 2019) - Kim, Young-Jin; Park, Junbeom; Jeong, Hyeon Su; Park, Min; Baik, Seulki; Lee, Dong Su; Rho, Heesuk; Kim, Hyungjun; Lee, Joong Hee; Kim, Seung-Min; Kim, Young-Kwan
Abstract : A seed-mediated growth of Au nanoparticle inside carbon nanotube fibers is investigated to enhance their performance. Abstract : The seed-mediated growth strategy of Au nanoparticles (Au NPs) inside carbon nanotube (CNT) fibers is demonstrated to greatly improve their mechanical and electrical properties and provide a function for catalytic applications. The resulting Au NP@CNT nanocomposite fibers exhibit 100% knot efficiency, catalytic activity and considerably enhanced modulus, tensile strength, and electrical conductivity from 7 GPa, 109 MPa and 1300 S cm −1 to 24 GPa, 351 MPa and 3600 S cm −1, respectively. The enhancement mechanism is also revealed by systematic characterization and theoretical simulations.